The Application of Social Survey Methods in Analysing the Tourist Activity of Seniors - Głąbiński Zbigniew (Bulletin of Geography. Socio-Economic Series)
The aim of the article is to discuss the possibilities of applying social research methods in the analysis of seniors' tourism activity. It emphasises the fact that research related to the participation of seniors in tourism is of major signifi-cance in many countries with rapidly changing population. The author mentions the methodological determinants of conducting social research that derive from two basic paradigms: quantitative and qualitative. Based on examples from the literature, the article presents the benefits and limitations of their use in conducting research on seniors' tourism activity. In the final part of the article, the author lists the methodological postulates regarding the implementation of the research among seniors as a specific segment of tourism activity.